Вдосконалення руху маршрутного автобуса у міських транспортних системах - Кравченко, Олександр; Чуйко, Сергій (Посвіт, 2019)
The reduction in the delay of the public transport bus traffic by means of the priority of the through signal that is based on using the transport-telematic system is proposed.
The improvement of the public transport bus traffic in the city transit systems
Keywords: 656.072.27